The Production of Pyocins of Pseudomonas aeruginosa: A Structure and Methodology Review: Pyocins Production: A review Study - Al-Mizel, Ali; Ajah, Hamzia Ali; Abudlrazaq, Raghad Abdullatif (ASJ - Academic Science Journal, 2025)
The main objective of this review is to clarify the definition, types and structures of pyocins. Italso highlights the various methods and their procedures that have been employed to screen,extract, isolate and purify pyocins from Pseudomonas aeruginosa. Furthermore, this studyprovides an analysis of the advantages and disadvantages associated with each approach. Thismay aid future research in combating antibiotic resistance that has become increasinglyprevalent in recent years creating a burden on both the medical and financial fronts. In recentyears, the resistance to antibiotics has increased rapidly due to the misuse and the presence ofinhibitory and sub-inhibitory concentrations of antibiotics in various terrestrial and aquaticenvironments. The misuse of these antibiotics has led to the emergence and spread of antibioticresistant microbes, posing challenges in treating common infections. The understanding ofthese findings is crucial for devising strategies to explore alternatives such as pyocins to replaceconventional antibiotics capable of efficiently combating bacterial illnesses. The studyconcluded that some techniques may not be very effective at differentiating between types ofpyocins though they are cheap which makes them beneficial for screening. On the other handother techniques accurately identify the pyocins, nevertheless, they are costly, complicated, andneed specific tools though some are more expensive than others. Some techniques lackspecificity, and left out centrifuge specifics that are essential to maintaining consistencybetween experiments. The initial ammonium sulphate saturation has not been mentioned and arange with ammonium sulphate precipitation with the highest yield should be measured.Numerous strains of indicators have been employed, indicating the necessity for more extensiveresearch to identify trustworthy indicators for consistent outcomes.